The Role of Artificial Intelligence in Teaching Foreign Languages: Enhancing and Shaping Students' Skills (Journal of the College of Basic Education, 2025)
The field of foreign language teaching is undergoing a major transformation thanks to recent technological developments. Artificial intelligence (AI) has become one of the essential tools that help improve the learning experience and develop various language skills. This research aims to analyze the role of AI in foreign language teaching, evaluate its effectiveness compared to traditional methods, and explore the benefits and challenges associated with its use. The importance of the current study lies in identifying the impact of AI on shaping and developing students' foreign language learning skills. The research relies on a descriptive approach and reaches several conclusions. AI enables a personalized learning experience tailored to each student's level, helping accelerate language acquisition. AI applications provide interactive environments for improving pronunciation and listening through voice assistants and pronunciation correction techniques. AI tools help improve grammar through automatic correction and text analysis. Interactive applications and educational games provide engaging ways to make language learning more fun and motivating. AI can be used in foreign language teaching.